EVALUATION THE CALCULATION OF WATERSATURATION WITH SIMANDOUX AND INDONESIA METHOD IN THE P LAYER R FIELD - Puri Wijayanti; Ratnayu Sitaresmi; Guntur Herlambang Wijanarko (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Logging Interpretation aims to determine petrophysical parameters such as volume shale, porosity, formation water resistivity used to calculate water saturation values. In this study the wells analyzed were four exploration wells. Log analysis carried out in this well is in the form of qualitative analysis and quantitative analysis. The average shale volume in KML-1, KML-2, KML-3 and KML-4 wells is respectively 0.172, 0.132, 0.167 and 0.115. The average effective porosity of KML-1, KML-2, KML-3 and KML-4 wells is 0.236, 0.268, 0.219 and 0.225 respectively. The values of a, m and n follow the lithology of the well, namely limestone (carbonate) with a value of 1, 2 and 2. The value of Rw is obtained from the Pickett Plot Method that is equal to 1.52 Ωm on KML-1, 1.52 Ωm on KML-2, 1 , 52 Ωm on KML-3 and 0.5 Ωm on KML-4. The average water saturation with the Simandoux Method in KML-1, KML-2, KML-3 and KML-4 wells is 0.336, 0.434, 0.670 and 0.397. While the average water saturation value with the Indonesian Method in KML-1, KML-2, KML-3 and KML-4 wells is 0.439, 0.488, 0.723 and 0.440 respectively. From the comparison with Sw Core, the Simandoux method is better used in calculating water saturation because the result is closer to the value of Sw Core.